2012
DOI: 10.1007/s11239-012-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical predictors of cardiac rhythm at 1 year follow-up in patients with non-valvular atrial fibrillation

Abstract: C-reactive protein (CRP) is increased in patients with atrial fibrillation (AF) and it might predict the lack of sinus rhythm maintenance in the long term follow-up. Scarce data have been reported relating endothelial dysfunction and/or haemostatic or platelet markers to sinus rhythm maintenance in AF patients. We aimed to determine whether some biochemical markers including soluble thrombomodulin (sTM), soluble P-selectin, thrombin-antithrombin (TAT) complex and CRP levels could predict sinus rhythm maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Patients with high CRP and high complement levels had a significantly higher risk of AF than did those with normal CRP and low complement levels; conversely, absent a high complement level, high CRP levels were not significantly associated with AF. 23 Acevedo and co-authors 29 compared the baseline CRP levels of 130 patients who had newly diagnosed nonvalvular AF with those of 20 healthy individuals and found that baseline CRP levels were significant and independent predictors of recurrent AF upon one-year follow-up examination, independent of other clinical and echocardiographic variables. Celebi and colleagues 30 evaluated the prognostic value of before-and after-cardioversion CRP levels in predicting the long-term risk of AF.…”
Section: Correlation Between Atrial Fibrillation and Inflammationmentioning
confidence: 99%
“…Patients with high CRP and high complement levels had a significantly higher risk of AF than did those with normal CRP and low complement levels; conversely, absent a high complement level, high CRP levels were not significantly associated with AF. 23 Acevedo and co-authors 29 compared the baseline CRP levels of 130 patients who had newly diagnosed nonvalvular AF with those of 20 healthy individuals and found that baseline CRP levels were significant and independent predictors of recurrent AF upon one-year follow-up examination, independent of other clinical and echocardiographic variables. Celebi and colleagues 30 evaluated the prognostic value of before-and after-cardioversion CRP levels in predicting the long-term risk of AF.…”
Section: Correlation Between Atrial Fibrillation and Inflammationmentioning
confidence: 99%
“…Recent data support the link of endothelial dysfunction with the pathophysiology of AF [1921]. Moreover, endothelial dysfunction is associated with higher risk of stroke [22] and lower probability of recovery of sinus rhythm in this patient group [19,23]. These observations indicate that endothelial dysfunction might represent the main link between epicardial fat and poorer prognosis for AF patients.…”
Section: Introductionmentioning
confidence: 68%
“…Of the 59 included studies, 35 studies investigated the association between platelet activation markers and AF, with a total of 2730 cases and 2371 controls [ 5 9 , 13 , 23 , 24 , 26 52 ]. There were 48 studies examining the association between coagulation activation markers and AF, including 5412 AF cases and 29292 controls [ 5 , 7 , 8 , 11 14 , 24 , 25 , 27 , 29 , 31 , 33 , 34 , 36 39 , 41 43 , 45 48 , 50 72 ]. A total of 11 studies investigated the association between fibrinolytic function markers and AF, with 631 patients and 6558 controls [ 11 13 , 31 , 45 , 50 , 59 , 61 , 63 , 67 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies investigated the association between fibrinolytic function markers and AF, with 631 patients and 6558 controls [ 11 13 , 31 , 45 , 50 , 59 , 61 , 63 , 67 , 72 ]. Finally, 19 studies examined the association between endothelial function markers and AF, with 2502 cases and 15289 controls [ 7 , 13 , 14 , 24 , 27 , 31 , 34 , 37 , 41 43 , 46 , 50 52 , 57 , 59 , 64 , 71 ]. The mean age of AF patients ranged from 37.0 to 81.5.…”
Section: Resultsmentioning
confidence: 99%